Cognitive restructuring in the level of depression in patients with HIV/SIDA - Moya Chávez, María Isabel (2008)
A quasi-experimental study, with before and after design, with ten participant between 18 to 60 years ( men and women) who assist VIH/SIDA program from a hospital center. The instruments applied were the Beck Depression inventory, 3 to 5 columns Data card of automatic thoughts and a Schedule of week activities, and as technique: observation, interview and experimentation. The results were concluding that after applying the Cognitive Restructuring Technique, the levels of depression in patients from the control and experimental group are significantly different, showing in the control group and increase of such levels. Likewise, the application of this technique is effective to diminish the levels of depression